Azaz Kebebasan Berkontrak dalam Islam (Pandangan Mazhab Hukum terhadap Kebebasan Membuat Syarat dalam Perjanjian) - Khusnul Khatimah (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2015)
Everyone wants to perform a variety of transactions and practices related to freedom and full flexibility. In Islam the transaction and an agreement on a contract is basically allowed for not taking someone else's property by false means. But the fuqana mazhab have different opinion on the conditions allowed and prohibited in the transaction or related even though there are similarities between them.